Perencanaan Formasi Pegawai Di Kanwil Badan Pertanahan Nasional Provinsi Jawa Tengah - Ridho, Faris; Warsono, Hardi; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
One of Bureaucracy Reforms coverage is to create quality human resources with high integrity in working with upholding professionalism , thus the need for a planning formationsto meet the quality and quantity of staff required. This study aimed to describe the formation of employee planning and supporting factors and obstacles encountered in planning theformation of an employee at the BPN of Central Java province.This study used a descriptive research with a qualitative approach . The focus of the study include: ( 1 ) formation of the planning process at the district office employees BPNCentral Java province , ( 2 ) the factors supporting and inhibiting the formation employee planning process .The results of the study planning process formation employee still needs to be improved in terms of analysis tools are available , the distribution of the workload of employees , budget efficiency , and analysis of employee turnover . Advice given is the BPN of Central Java province should be more effective in forecasting the division of labor and employees who will be out.